Life-History Traits and Population Relative Fitness of Trichlorphon-Resistant and -Susceptible Bactrocera dorsalis (Diptera: Tephritidae) - Zhang Yu-ping; Lu Yong-yue; Zeng Ling; Liang Guang-wen (Psyche: A Journal of Entomology)
Life tables were established for trichlorphon-resistant and susceptible Bactrocera dorsalis strains based on the laboratory observations. Trichlorphon-resistant B. dorsalis strain had longer pupal and preoviposition periods, and mean generation time compared to the trichlorphon susceptible strain. Lower fecundity, emergence rate, and probability of standard fecundity PF, and shorter female and male longevity also were apparent in the trichlorphon resistant strain. Based on the life tables, the life population trend index (I) of the resistant strain was 86.80, while that of the susceptible strain was 116.97. The net reproduction rate (R0) and the intrinsic rate of increase (rm) of the resistant strain were 1565.33 and 0.0164, while those of susceptible strain were 2184.00 and 0.0173, respectively. The results from this research revealed that the resistant strain was at a reproductive and developmental disadvantage relative to the susceptible strain.